2005
DOI: 10.1007/s10195-005-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of growth factors in ACL surgery: preliminary study

Abstract: There is no general consensus on the use of growth factors (GF) in surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 9 publications
(10 reference statements)
3
76
0
2
Order By: Relevance
“…Regarding ACL graft maturation, there is some promising evidence that the addition of PRP to the graft or tunnels could be a synergic factor in acquiring maturity more quickly than grafts with no PRP. 10,13,20,22 There were 2 studies that showed a tendency toward this outcome, but the small sample size numbers probably made it difficult to obtain statistically significant differences between the groups. 16,21 There was 1 study that showed no differences regarding maturation when using or not using PRP in ACL reconstruction.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Regarding ACL graft maturation, there is some promising evidence that the addition of PRP to the graft or tunnels could be a synergic factor in acquiring maturity more quickly than grafts with no PRP. 10,13,20,22 There were 2 studies that showed a tendency toward this outcome, but the small sample size numbers probably made it difficult to obtain statistically significant differences between the groups. 16,21 There was 1 study that showed no differences regarding maturation when using or not using PRP in ACL reconstruction.…”
Section: Discussionmentioning
confidence: 86%
“…Ventura et al, 10 regarding graft maturation, presented CT data that showed a significant difference between groups (P < .01), with PRP ACL graft similar to native ACL tissue, whereas untreated grafts showed a more heterogeneous nature. From the clinical aspect, they found no differences in Knee Injury and Osteoarthritis Outcome Score, KT-1000 measurement, or Tegner score between the PRP group and control group at 6 months.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Biological signalling proteins are the driving force behind growing number of groups working on the use of platelet-rich plasma (PRP) as an adjunct treatment after surgery [19,29,34,35,40]. However, it is noteworthy that recent articles appear not to have found bone tunnel widening reduction with PRP [29,39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been seen that the PRP is useful in chronic Achilles tendinopathy especially when infiltrations Ozone [8,9,10], patellar tendinopathy [5,6,11], previously used in repairing cuff rotators [12,13,14], repair the anterior cruciate ligament [11] or with plasty erector or tibial bone-tendon graft-bone, meniscal repair the knee joint [5,6], in the reconstruction of the glenoid labrum or hip and ultimately partial and total muscle injury made here open repair and strengthening PRP later [7,19].…”
Section: Other Applicationsmentioning
confidence: 99%